Do additional full-length radiographs of the humerus and forearm improve the decision making in children with supracondylar humerus fractures?. Issue 5 (September 2016) - Bloom, Tamir; Seigerman, Daniel A.; Zhao, Caixia; Sabharwal, Sanjeev
Abstract : We sought to determine the diagnostic utility of additional full-length radiographs of the forearm and humerus for pediatric supracondylar humerus fractures. A pediatric orthopedic surgeon and a senior orthopedic resident individually reviewed the initial humerus, forearm, and elbow radiographs of 55 children with a supracondylar humerus fracture and recommended definitive treatment (operative vs. nonoperative) on the basis of the modified Gartland classification. Interobserver agreements for classification and the recommended treatment were highest for the elbow radiographs (weighted κ =0.92). All disagreements in the recommended treatment were in fractures classified as Gartland type I versus II fractures. Although two children (4%) had an ipsilateral distal forearm fracture, selective versus routine use of additional full-length radiographs in children with a supracondylar humerus fracture needs to be evaluated further.